Insulated molecular wires. - Frampton, M; Anderson, H (2007)
An astonishing assortment of structures have been described as "insulated molecular wires" (IMWs), thus illustrating the diversity of approaches to molecular-scale insulation. These systems demonstrate the scope of encapsulation in the molecular engineering of optoelectronic materials and organic semiconductors. This Review surveys the synthesis and structural characterization of IMWs, and highlights emerging structure-property relationships to determine how insulation can enhance the behavior of a molecular wire. We focus mainly on three IMW architectures: polyrotaxanes, polymer-wrapped pi systems, and dendronized polymers, and compare the properties of these systems with those of conjugated polymers threaded through mesoporous frameworks and zeolites. Encapsulation of molecular wires can enhance properties as diverse as luminescence, electrical transport, and chemical stability, which points to applications in electroluminescent displays, sensors, and the photochemical generation of hydrogen.